Nilai-Nilai Pendidikan Islam Dalam Novel “Laut Tengah” Karya Berliana Kimberly - Latifah Sriwijaya; Ali Imron; Muhammad Saefullah (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
The objectives of this study are: (1) to understand the content of the novel Laut Tengah by Berliana Kimberly; (2) to identify the Islamic educational values contained in the novel Laut Tengah by Berliana Kimberly; and (3) to determine the relevance of the Islamic educational values found in the novel Laut Tengah by Berliana Kimberly to education in Indonesia. This research employs a qualitative approach. By type, it is classified as library research. The data sources consist of two types: primary and secondary. The primary data source is the novel Laut Tengah by Berliana Kimberly, while secondary data sources are obtained from various other literature such as books, articles, and journals discussing Islamic educational values. The data collection technique used is documentation, namely collecting books, articles, journals, and scholarly works relevant to this research. The data analysis technique applied is content analysis, which aims to analyze and interpret the messages contained in the data. The study finds that the novel Laut Tengah contains three main aspects of Islamic educational values. First aqidah (faith, including tawakal (reliance on Allah) and belief in Allah’s help. Second, ibadah (worship) values, comprising prayer (salat), dhikr (remembrance of Allah), supplication (doa), seeking forgiveness (istighfar), reading the Qur’an, tahajjud (night prayer), istikharah (prayer for guidance), and the intention to seek knowledge as an act of worship. Third, akhlak (moral) values, divided into akhlak toward Allah, akhlak toward fellow humans, and social akhlak. The novel has strong relevance to education in Indonesia, encompassing the spiritual aspect, self-control aspect, noble character aspect, intellectual aspect, and skills and responsibility aspect (e.g., mastering foreign languages, being responsible as the head of a family). Thus, this novel is worthy of being used as enrichment material or a learning medium in Islamic education in Indonesia.